Special exercises using the strength training balanced rate according to some kinematic variables and their impact in the muscular balance and pull young weightlifters - hashim fenjan, Falih; abdulwahab ismaeel, Safaa; M. Ahmed, Ali. (International Journal of Psychosocial Rehabilitation, 2020)
Through the results of note the obvious development in search of kinematic variables reduce the differences between the two sides of the gravity of the land rises from the first stage to the end of the advancement of installation, the researchers attribute this development to the precise diagnosis by imaging and analysis of the performance of skilled and appropriate exercises As mentioned that the kinesthetic analysis performance study of skilled care for the athlete and give the proper analysis of each part of the skill in the form in which the coach helps diagnose errors and develop appropriate solutions" if that change in reducing differences in weight gains of the two sides to exercise used on the device and the active role of this ratio by making it harder for performance on the device that makes weightlifter makes a major effort to cut the balance to overcome external defenses and how to The division of effort on both sides of the body and this was confirmed by the to keep the muscles in the case of true balance with increasing force and increasing the range of muscles and joints activist is the first requirement for the development of the vulnerability of the development of the balance.